THE MOSCOW AMBULANCE STATION. FROM THE SOURSE TO THE PRESENT - N. F. Plavunov; L. F. Verkhoturova; V. A. Kadyshev; A. N. Rozhenetskij (SINAPS LLC, 2017)
This article is devoted to 130th anniversary and publication of academic writings of Alexander Puchkov - Doctor of Med. Sci., Honored Doctor of Russian Soviet Federative Socialist Republic. He was permanent leader of Moscow Ambulance Station from 1923 to 1952. Data presented in Puchkov's articles were used to compare performance of work of Moscow ambulance in it's formative period and our days. This article shows specificities, characteristics and environment of Moscow ambulance in 1926 and 2016. For example, the number of brigades had increased by 67,9 times (from 15 in 1926 to 1018 in 2016). Average time of arrival to accident is 10-12 minutes is same for 1926 and 2016. The proportion of pediatric interventions (from birth to 15 years old) had increased. Analysis of indicators allows to look at development of Moscow ambulance station from it's formative period to our days. Fundamental principles laid down by A. Puchkov last in many cases in work of Moscow Ambulance in our days. Ambulance doctors continue to provide medical assistance promptly in the framework spelt out more than 90 years ago.